FEATURES OF THE STATE OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH CHRONIC PANCREATITIS - Turakulov Rustam Ismatillaevich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Over the past 30 years, there has been a worldwide tendency towards an increase in the incidence of acute and Chronic pancreatitis Acute Pancreatitis and CHRONIC PANCREATITIS by more than 2 times. If in the 80s the frequency of CHRONIC PANCREATITIS was 3.5-4.0 per 100 thousand of the population per year, then in the last decade there has been a steady increase in the frequency of pancreatic diseases, affecting 8.2-10 people per 100 thousand of the worlds population annually. The prevalence of CHRONIC PANCREATITIS in Europe is 25.0-26.4 cases per 100 thousand population. The prevalence of CHRONIC PANCREATITIS in adults is 27.4-50 cases per 100 thousand population.